Characterization, antibacterial, total antioxidant, scavenging, reducing power and ion chelating activities of green synthesized silver, copper and titanium dioxide nanoparticles using Artemisia haussknechtii leaf extract. (17th November 2018) - Alavi, Mehran; Karimi, Naser
Abstract: Recently, major problem related to pathogenic bacteria is augmentation of antibiotic resistance which has been changed treatment and recovery of millions of infectious patients. The present study reports an eco-friendly, rapid and easy method for synthesis of silver (Ag), copper (Cu) and titanium dioxide (TiO2 ) nanoparticles (NPs) using Artemisia haussknechtii leaf aqueous extract with antibacterial activities against multi-drug resistance (MDR) bacteria species. Three different concentrations (0.001, 0.01 and 0.1 M) of AgNO3, CuSO4 and TiO (OH)2 were investigated for obtaining optimum NPs green synthesis. Total phenolic content, total flavonoid content of leaf extract and total antioxidant activity (DPPH) assay were determined as radical scavenging methods. UV–Visible spectroscopy, Fourier transform infrared spectroscopy analysis, X-ray diffraction, energy dispersive X-ray spectroscopy, field emission scanning electron microscope and atomic force microscopy (AFM) were used due to NPs characterization. The size average of the Ag, Cu and TiO2 NPs obtained were respectively 10.69 ± 5.55, 35.36 ± 44.4 and 92.58 ± 56.98 nm. In the case of antibacterial assay, disc diffusion assay, minimum inhibitory concentration, minimum bactericidal concentration, bacterial growth and morphology of four MDR species Staphylococcus aureus ATCC 43300, Staphylococcus epidermidis ATCC 12258, Serratia marcescens ATTC13880 and Escherichia coli ATCC 25922 were evaluated. Results of this study demonstrated that A. haussknechtii leaf extract with various groups of phytochemicals such as phenols and flavonoids had suitable ability in green synthesis of Ag, Cu and TiO2 NPs. Also, Ag and Cu NPs had more antibacterial activities compared to TiO2 NPs.